Incongruity between pedagogy of authenticity and contemporary educational apparatus: person-centred phenomenological studies - Plust, Urszula (2023)
While individual motivations can vary greatly, becoming a teacher is commonly conceptualised as a socially constructive choice. Using the concept of teachers’ authenticity, this doctoral work examines that notion in the lived experiences of teachers working in England. This examination occurs in selfemerging stages, as a consequence of pursuing a person-centred understanding of teacher’s authenticity as a socially constructive pedagogy and its viability in context of contemporary education.